(3QSGdI aj GdUdGIs - (3eLghds
(3ChdgG (B:s
... (3hZjQgeG ef GdfU Ydi HWdGf GdWgGQI hCOGA GdRcGI hfMhgG CeG GdUhe ajUM dCfg dG jONd ddchf ajg hdjS aYdG hfMhg aj GdOQhS hGdehLR hGdQhV hZjQgG Hd aj GdCNjQ hbO jTcd aj GdUhe HGYJHGQ GdfjI aEfgG aYd (B...s
(3BNQgG (B:s
... (3HebfVi JQc (B.. (3hZjQg hdPG CWdb GdCUMGH ceG aj cTa GdeKGe hajge eOYh GdELeGY Hd Yf GdeSGdc GdELeGY Ydi GdEWdGb hgh NjQI cKjQI eff JCNQ hdcf aj GdbhGYO hGddeYI hZjQgeG (B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis